Learning to Prevent Grasp Failure with Soft Hands: From Online Prediction to Dual‐Arm Grasp Recovery. (7th October 2021) - Averta, Giuseppe; Barontini, Federica; Valdambrini, Irene; Cheli, Paolo; Bacciu, Davide; Bianchi, Matteo
Abstract : Soft hands allow to simplify the grasp planning to achieve a successful grasp, thanks to their intrinsic adaptability. At the same time, their usage poses new challenges, related to the adoption of classical sensing techniques originally developed for rigid end defectors, which provide fundamental information, such as to detect object slippage. Under this regard, model‐based approaches for the processing of the gathered information are hard to use, due to the difficulties in modeling hand–object interaction when softness is involved. To overcome these limitations, in this article, we proposed to combine distributed tactile sensing and machine learning (recurrent neural network) to detect sliding conditions for a soft robotic hand mounted on a robotic manipulator, targeting the prediction of the grasp failure event and the direction of sliding. The outcomes of these predictions allow for an online triggering of a compensatory action performed with a second robotic arm–hand system, to prevent the failure. Despite the fact that the network is trained only with spherical and cylindrical objects, we demonstrate high generalization capabilities of our framework, achieving a correct prediction of the failure direction in 75 % of cases, and a 85 % of successful regrasps, for a selection of 12 objects of common use. Abstract : Herein, an innovative combination of tactile sensing and gated recurrent unit networks is proposed to detect when and in which direction an object is falling from a soft robotic hand. The outcomes of these predictions allow for an online triggering of a compensatory action performed with a second robotic arm–hand system, to prevent the failure.